A flowing partially penetrating well in a finite-thickness aquifer: a mixed-type initial boundary value problem - Chang, Chien-Chieh; Chen, Chia-Shyun (Journal of hydrology (Amsterdam), 2003)
An analytical approach using integral transform techniques is developed to deal with a well hydraulics model involving a mixed boundary of a flowing partially penetrating well, where constant drawdown is stipulated along the well screen and no-flux condition along the remaining unscreened part. The aquifer is confined of finite thickness. First, the mixed boundary is changed into a homogeneous Neumann boundary by discretizing the well screen into a finite number of segments, each of which at constant drawdown is subject to unknown a priori well bore flux. Then, the Laplace and the finite Fourier transforms are used to solve this modified model. Finally, the prescribed constant drawdown condition is reinstated to uniquely determine the well bore flux function, and to restore the relation between the solution and the original model. The transient and the steady-state solutions for infinite aquifer thickness can be derived from the semi-analytical solution, complementing the currently available dual integral solution. If the distance from the edge of the well screen to the bottom/top of the aquifer is 100 times greater than the well screen length, aquifer thickness can be assumed infinite for times of practical significance, and groundwater flow can reach a steady-state condition, where the well will continuously supply water under a constant discharge. However, if aquifer thickness is smaller, the well discharge decreases with time. The partial penetration effect is most pronounced in the vicinity of the flowing well, decreases with increasing horizontal distance, and vanishes at distances larger than 1–2 times the aquifer thickness divided by the square root of aquifer anisotropy. The horizontal hydraulic conductivity and the specific storage coefficient can be determined from vertically averaged drawdown as measured by fully penetrating observation wells. The vertical hydraulic conductivity can be determined from the well discharge under two particular partial penetration conditions.